STRATEGI KEPOLISIAN RESORT KOTA PONTIANAK DALAM MENJAGA KETERTIBAN PADA PENYELENGGARAAN PEMILIHAN UMUM (Studi Pemilihan Umum Presiden 2014) - HUJRA SOUMENA,S.Ik. A.2021131086, Jurnal Mahasiswa S2 Hukum UNTAN (Jurnal NESTOR Magister Hukum, 2015)
ABSTRACThis thesis discuss strategy Pontianak City Police in maintaining order on the organization of elections (Presidential Election Study 2014). In order to secure the implementation of the Presidential Election 2014 Police Pontianak organizing internally that is organizing the parts and units Operational Police Pontianak become a united force and coordinated properly it is also necessary organizing externally that the City Government of Pontianak, KPU Pontianak, Pontianak city Supervisory Committee, Organizing Committee for the 2014 presidential election and Community Potential in an integrated and coordinated systematically according to the task, role, functions and responsibilities of each in relation to the implementation pemelihan pressiden 2014. The dominant factor affecting the implementation of the 2014 Presidential Elections Police Pontianak and public order are primed in Pontianak Police region are: geographical conditions very broad Pontianak City 107.82 km2, with a population of 550 304 inhabitants. While the number of Police personnel Pontianak just as much as 1331 personnel, is certainly not sufficient to Pontianak Police efforts in protecting, nurturing and serving the people of the city of Pontianak in the face of the organization of the election year 2014.Kondisi jobs in Pontianak are still limited or not comparable with the needs of the population to get decent work in various sectors of life, has the potential to create interference in the administration of the 2014 presidential election in the City of Pontianak.Kondisi socio-economic, socio-political and socio-cultural in Pontianak are still vulnerable to the dynamics of democratic life that deviate from the values of moral, religious, social, and applicable laws and regulations, can trigger horizontal conflict and / or crime-impact kontijensi.Strategi strategy lakukakan by Pontianak City Police in maintaining maintaining order on the implementation of the 2014 presidential election through prevention, deterrence and prevention of crime to support the implementation of the general election president in 2014 conducive manner: Improving the implementation of the policing function optimally, a partnership Police with the City of Pontianak, KPU Pontianak, Panwaslu Pontianak City and related institutions, establish partnerships Police with the Community, as well as improve the ability, character, identity and professionalism Police personnel on an ongoing basis. Doing deterrence, the condition of the